Feasibility Analysis of Smelter Grade Alumina (SGA) Project Development at PT. X - Dio Rianto; Dedy Setyo Oetomo; Rizky Fajar Ramdhan (Sainteks: Jurnal Sain dan Teknik, 2023)
Abstract: Indonesia has a wealth of promising natural resources in the form of minerals and coal such as bauxite. Considering that the government is planning to stop bauxite exports and increase domestic processing or downstreaming. So it is necessary to carry out a factory financial feasibility analysis for processing bauxite into alumina or Smelter Grade Alumina (SGA) at PT.X. Feasibility analysis using a reference capacity of 1,000,000 tons of alumina. The parameters used to determine the financial feasibility analysis in alumina production at PT. X are Net Present Value (NPV), Internal Rate Return (IRR), Payback period (PP). Based on the results of the analysis research, it was obtained that the total cost of CAPEX (Capital Expenditure) that had to be spent was Rp. 7,057,514,558,158 and the total OPEX (Operational Expenditure) costs that must be incurred is Rp. 1,479,733,686,519 with a Net Present Value of Rp. 208,752,623,349, the Internal Rate of Return is 15%, and the Payback Period is 8 Years and 3 Months, so the project is feasible to run.